2017
DOI: 10.1016/j.jesf.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen delivery is not a limiting factor during post-exercise recovery in healthy young adults

Abstract: PurposeIt is still equivocal whether oxygen uptake recovery kinetics are limited by oxygen delivery and can be improved by supplementary oxygen. The present study aimed to investigate whether measurements of muscle and pulmonary oxygen uptake kinetics can be used to assess oxygen delivery limitations in healthy subjects.MethodsSixteen healthy young adults performed three sub-maximal exercise tests (6 min at 40% Wmax) under hypoxic (14%O2), normoxic (21%O2) and hyperoxic (35%O2) conditions on separate days in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In both conditions, the participants performed maximal cycling which resulted in successive intense ischemic episodes in the exercising muscle (i.e., StO 2 < 20%, Figure 4A ). Previous studies have evaluated muscle reoxygenation responses (oxygen delivery to tissues) after exercise ( Kemps et al, 2009 ; Mankowski et al, 2017 ; Zebrowska et al, 2021 ), and confirmed the validity and utility of NIRS device when assessing individuals’ recovery kinetics between different oxygen levels ( Mankowski et al, 2017 ). Arterial inflow to thigh muscles may have increased during recovery irrespective of different oxygen recovery conditions, and that normoxic recovery further enhanced these responses compared to hypoxic recovery, probably due to greater arterial O 2 supply (higher arterial O 2 content).…”
Section: Discussionmentioning
confidence: 73%
“…In both conditions, the participants performed maximal cycling which resulted in successive intense ischemic episodes in the exercising muscle (i.e., StO 2 < 20%, Figure 4A ). Previous studies have evaluated muscle reoxygenation responses (oxygen delivery to tissues) after exercise ( Kemps et al, 2009 ; Mankowski et al, 2017 ; Zebrowska et al, 2021 ), and confirmed the validity and utility of NIRS device when assessing individuals’ recovery kinetics between different oxygen levels ( Mankowski et al, 2017 ). Arterial inflow to thigh muscles may have increased during recovery irrespective of different oxygen recovery conditions, and that normoxic recovery further enhanced these responses compared to hypoxic recovery, probably due to greater arterial O 2 supply (higher arterial O 2 content).…”
Section: Discussionmentioning
confidence: 73%